FERMENTATION IN SALT SOLUTION TO PRODUCE JACK BEANS (Canavalia ensiformis L) SAUCE - Yusman Taufik, Yudi Garnida (Proceeding of International Congress, 2014)
The purpose of this research was to determine the proportion or optimal formulation so as to produce jackbean sauce best quality using Design Expert DâOptimal method. This research uses statistical data processingprogram for which the software Design Expert 7.0.0 with Mixture Dâoptimal design to design variablethe jack bean (X1), concentration of salt (X2), Rhizopus sp (X3), garlic (X4), coriander (X5), anise(X6), turmeric (X7), bay leaves (X8), leaves of lemongrass (X9), galangal (X10), MSG (X11), brown sugar(X12), and keluak (X13). Analyzed response were cyanide acid content, protein content, water content,total dissolved solids, viscosity, flavor, color, consistency, and aroma. Selected jack bean sauce withoptimal formulation is sauce with the following composition jack bean 12,5%; salt solution 20%; Garlic1,1%; coriander 0,5%; anise 0,05%; turmeric 0,5%; bay leaf 0,6%; lemongrass leaves 0,6%; galangal 1,2%;MSG 0,4%; brown sugar 60,5%;keluak 2%. The formulation has been predicted by the program with levelsof cyanide 13,79 mg/kg; protein content of 3,46%; water content of 28,16%; total dissolved solids 20.58 oBrix; viscosity 21.91 d.Pa.s; the flavor attribute scores 4.52; the color attributes score 4.55; the viscosityattributes scores on 3.96; and the aroma attributes score 3.63.Keywords: Formulation; Jackbeans; Soy Sauce; Design Expert; DâOptimal.